The Study of Speaking Ability in ASD (Autistic Speacktrume Disorder) Children at An Elementary School: Penelitian Kemampuan Berbicara Pada Anak ASD (Autistic Speacktrume Disorder) di Sekolah Dasar - Karina Anis; Kemil Wachidah (Universitas Muhammadiyah Sidoarjo, 2022)
The study of speaking ability in ASD (Autistic Speacktrume Disorder) children at SDN Gedangan Sidoarjo aims to describe 1) Pronunciation of ASD (Autistic Speacktrume Disorder) children when speaking at school, 2) ASD children's vocabulary (Autistic Speacktrume Disorder) when speaking at school, 3) The facial expression or facial expression of ASD (Autistic Speacktrume Disorder) children when speaking at school. This study uses a qualitative case study type. The subjects of this study were children with special needs in the ASD (Autistic Speacktrume Disorder) category in grades IV and V. The object of this study was the speaking ability of children with autism ASD (Autistic Speacktrume Disorder) at school. Research data collection techniques using observation, interviews and documentation. The data obtained by the study were analyzed using data reduction, presentation and drawing conclusions. The process of checking the validity of the data uses technical triangulation. The form of communication that ASD (children can doAutistic Speacktrume Disorder) when speaking at school is using one-way communication from the researcher to the subject. So it still requires guidance. They are able to respond to communication when the interaction takes place, but sometimes the responses given are not in accordance with the topic of communication. The responses given tend to be nonverbal communication such as touch and gestures